The relationship of selected maternal exposures and the delivery of low birth weight infants - Tabarejo, Crisol T. Jalando-on
This hospital-based case-control study was conducted 1) to describe the association between maternal nutrition, physical activity, maternal smoking, passive smoking and the delivery of low birth weight infants; 2) to estimate the etiologic fraction that may be attributed to each of the risk factors of interest. The study subjects were composed of 246 prevalent cases of low birth weight infants and 246 control infants who were delivered full term, live, singleton by multiparous mothers without maternal and medical complications.Based on the results of the multivariate analyses, maternal undernutrition and strenuous physical activity were statistically associated with the delivery of low birth weight infants. The adjusted Odds Ratios were 6.118 (95C.I. ORMH 2.416-15.31) and 3.646 (95C.I. ORMH 2.391-5.560), respectively. Maternal smoking was also associated with the delivery of low birth weight infants with an ORMH=2.354 (95C.I. ORMH=.9943-5.851) but this result was not statistically significant. The etiologic fraction attributed to maternal undernutrition, strenuous physical activity, and maternal smoking were 85.969.6and 59.8, respectively.The findings of this study are valuable for maternal care gives in monitoring and identifying mothers who may need special care. With proper training of health workers, MUAC can be utilized to identify pregnant women at risk earl during pregnancy. The result can also aid in preparing practical, low-cost nutrition plan for pre and postnatal care of mothers to improve birth outcome in close successive pregnancies. Health workers should educate mothers of the possible harmful effects of strenuous physical activities during the third trimester of pregnancy. Maternal caregivers may recommend to employers to consider modification of the strenuous activities of pregnant women employees identified at-risk of low birth weight. The deleterious effect of maternal smoking on both the fetus and the mother's health should be emphasized to pregnant mothers.